ANALYSIS OF STUDENT BEHAVIOR IN MIRAS UTILIZATION IN MADRASAH ALIYAH STATE 1 COST OF BUOL DISTRICT - Arpin (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to analyze student behavior in alcohol abuse at Madrasah Aliyah Negeri 1 Biau, Buol Regency. The type of qualitative research with a case study approach with a sample of 5 informants. Data collection was carried out through in-depth interviews. The data analysis technique used the content analysis method to identify topics or categories in the data. The results of this study indicate that knowledge, attitudes, family roles, and the role of the principal influence student behavior in alcohol abuse in the school environment. of the 5 informants, 4 informants did not know at all the dangerous impacts of alcohol abuse, they only knew the pleasure when consuming it, while 1 informant was able to mention the signs, namely unconsciousness which could threaten the informant's life. Meanwhile, the attitude of informants when invited to consume alcohol in the school environment during school hours, 2 informants refused on the grounds that their parents did not give them pocket money and they were presenting religious memorization. The involvement of students in the abuse of alcohol in the school environment, is very disturbing to the parents of respondents, the principal along with teachers and staff at Madrasah Aaliyah Negeri 1 Biau. The school in this case the principal strongly condemns its students consuming alcohol in the school environment.